A comprehensive review of the neurological effects of anethole - Ramina Khodadadian; Shima Balali- Dehkordi (IBRO Neuroscience Reports)
Since ancient times many countries have employed medicinal plants as part of traditional medicine. Anethole is a substance found in various plants and has two isomers, cis-anethole (CA) and trans-anethole (TA). Currently, the food industry extensively use anethole as an aromatic and flavoring component. Extensive scientific research are warranted to provide scientific proof for the usage of anethole, given its widespread use and affordable price. Preclinical studies have suggested several pharmacological effects for anethole including neuroprotective properties. It has been determined that anethole through modulation of monoamines, gamma-aminobutyric acid (GABA)ergic and glutamatergic neurotransmissions as well as its possible anti-inflammatory and antioxidative stress properties affected central nervous system (CNS). In this concept previous studies have demonstrated anxiolytic, antidepressant, antinociceptive, anticonvulsant, and memory improvement effects for anethole. To fully understand its therapeutic potentials, more research are required to elucidate the precise mechanisms by which TA and CA affected CNS. This review summarizes the current knowledge on pharmacological activities of the anethole concentrating its neurological properties, and the possible mechanisms underlying these effects. Various pharmacological effects which have been reported suggesting that anethole could be considered as a potential agent for management of neurological disorders.